Intelligent systems and artificial intelligence to enhance customer segmentation - Lopes da Costa, R.; Gonçalves, R.; Fachada, B.; Pereira, L.; Dias, Á. (International Journal of Business Information Systems, 2025)
This study investigates how artificial intelligence, its characteristics, features and limitations enhance customer segmentation. All these aspects were analysed through literature review and were further developed by two methodologies: online questionnaire and interviews. The online questionnaire concluded that, while artificial intelligence's characteristics and impacts positively influence its implementation in customer segmentation, this type of technology still has limitations that could constitute an obstacle. Regarding the interviews, the main insight was that artificial intelligence is still only perceived as a support in decision making, thus, dependent on humans. However, many employees still look at these technologies as a threat to their workplace, which can lead to resistance in their implementation and incur on unnecessary costs for organisations.